PENGEMBANGAN MODEL RESISTENSI TERHADAP SISTEM INFORMASI AKADEMIK JURUSAN KEBIDANAN POLITEKNIK KESEHATAN KEMENKES SURABAYA - Heru SWN; Sunarto .; Subagyo .; Nuryani . (JURNAL PENELITIAN KESEHATAN, 2015)
mplementation of management information systems based on information technology is absolutelynecessary for the organization, including health education institutions. Jurusan Kebidanan PoltekkesKemenkes Surabaya faces obstacles in the implementation of academic information system that is userresistance, especially at the level of behavior apathetic and passive resistance. The purpose of thisresearch is to develop models of user resistance to the implementation of academic information systems.The population of this cross-sectional study was lecturers, staffs, and students in the Jurusan KebidananPoltekkesKemenkesSurabaya. Sample size'is 320, which is taken with proportionated sampling technique.There were 7 variables proposed as determinants of user resistance, include: lack of user education andtraining (LUET), change in job content (OC), usability issues and resistance to technology (UIRT), lack ofuser involvement in the development process (LUID), and lack of communication between topmanagement and end-user (LCMU), increased effort (IE), and user expectation (EU). Data were collectedthrough questionnaires, and then analyzed using path analysis. LCMUnot proven as a determinant of userresistance. Direct determinants for user resistance were IE and EU. IE was influenced directly by UIRT andinfluenced indirectly by LEUT and OC, while the EU was influenced directly by LUID. User resistanceinvolves two direct determinants namely IE and UE and four indirect determinants namely LUET, OC,UIRT, and LUID. Implementation of information systems need to be supported by: 1) training andassistance in the face of changes in job content and the issue of resistance, in order to reduce the efforttoo hard, 2) user involvement in the development of the system, so that user expectations easily realized.Key words: Information systems, user resistance, increased effort, user expectation.